MENINGKATKAN KUALITAS HIDUP PASIEN HEMODIALISA DENGAN MENURUNKAN KECEMASAN DAN MENINGKATKAN DUKUNGAN KELUARGA - Kusyani, Asri; Sekar, Diah Sari; Kurniawan, Vendi Eko; Sutomo, Hadi (LPPM STIKes Bahrul Ulum Jombang, 2018)
Chronic renal failure results in progressive and irreversible renal dysfunction, so that Hemodialysis patients experience symptoms of anxiety and decreased quality of life. quality of life is the perception of the individual in the ability of the limitations, symptoms and psychosocial nature of his life in the cultural context (physical, psycho, social, environment, spiritual). The quality of life of CKG patients with hemodysis therapy is still an interesting issue by health professionals. Low quality of life will improve hospitalization and mortality in hemodialysis therapy patients. The purpose of this study is to improve the quality of life of hemodialysis pasein by increasing family support and decreasing anxiety of Hemodialisa Patients In Hemodialisa Unit of RSUD Jombang. The design of this research is Correlation Analysis with Cross Sectional approach. The population of hemodialysis patient in hemodialysis room of RSUD Jombang was 160 patients, sampling technique used quota sampling and got 32 respondents. Data was collected using a family support questionnaire, ZSRAS scale and WHQOL-BREF questionnaire analysis using spearmen rank correlation test. The result of correlation analysis between family support and quality of life is obtained ρ value = 0,029, number 0,029 <α (0,05) which means there is relationship between family support and quality of life. And the result of correlation between anxiety with quality of life obtained ρ value = 0.013, number 0.0013 <α (0.05) which means there is a relationship between anxiety with quality of life. Based on this it can be concluded that family support and anxiety levels of patients in hemodialysis are important factors that must be considered to improve the quality of life of dihemodialisa patients. health personnel, especially nurse hemodialisa should provide health education by providing support, both management support, environment and stress so that the patient's anxiety can be reduced, there by improving the quality of life of hemodialysis patients despite physical limitations.